Short-run structural rigidities and supply performance in a financially repressed economy: |the case of Turkey - Doğruel, A. Suut. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
In the beginning of the 1980, a stabilization prograrrce was introduced fulder the auspices of the IMF as a remedy to high rate of inflation and excessive balance of payment deficits experienced in Turkey. After five-year implementation, however, the success of the programme is ambiguous. The purpose of the study is to evaluate the short-run rigidities as an obstacle to stabilization efforts experienced last years from the "structuralist" perspective. The emphasis given solely on the supply side. But, due to their direct effects on the supply side, the external balance and the adjustment mechanisms in the financial sector are also included. Simple rr:acroeconomic models are presented in the study and used for explaining some of the stylized. facts of the Turkish economy. A macroeconometric model for the Turkish economy is estimated and used for analyzing some of the structural characteristics of the economy the study concerns.
Keywords: Industrialization -- Turkey.